General health of students of medical sciences and its relation to sleep quality, cell phone overuse, social networks and internet addiction - Rasool Kawyannejad; Maryam Mirzaei; Ali Valinejadi; Behzad Hemmatpour; Hasan Ali Karimpour; Javad AminiSaman; Ebrahim Ezzati; Siavash Vaziri; Mojgan Safaeepour; Saeed Mohammadi (BioPsychoSocial Medicine, 2019)
Abstract Background In recent years, the phenomena of access to the cell phone and addiction to the Internet have been developed among students due to their many applications and attractiveness. Therefore, the present study was conducted with the aim of evaluating general health status and also determining the predictive role of variables such as cell phone usage, sleep quality, internet addiction and social networks addiction in students. Methods This cross-sectional study was conducted on 321 students of Kermanshah University of Medical Sciences in an analytical approach. Data collection tools were: Goldberg’s General Health Questionnaire, Pittburgh Sleep Quality Index, Young Internet Addiction Test, Social Network Addiction Questionnaire, and Cell Phone Overuse Scale. Data analysis was done using SPSS version 21 and general linear model. Results Based on the results, the mean (SD) score of the general health was 21.27 (9.49). Variables of gender, sleep quality, and levels of cell phone usage were independent predictors of student’s health. Male students (β (95% CI) = − 0.28 (− 0.49 to − 0.01) and students with favorable sleep quality (β (95% CI) = − 0.22 (− 0.44 to − 0.02) had lower total health score than the reference category (female students and students with unfavorable sleep quality, respectively). In addition, students with cell phone overuse (β (95% CI) = 0.39 (0.08 to 0.69) had a higher general health score than the reference category (students with cell phone little use). In general, this group of students had lower general health status (Low or high scores of general health indicate a higher and lower general health status for subjects, respectively). Conclusion Variables of gender, sleep quality and cell phone use were the most important variables associating the general health of medical students.